Prediksi Harga Bitcoin Menggunakan Metode ARIMA - Ebenhasier Liunokas; Kresentius Iku Kobesi; Cecilia Novianti Salsinha (Journal of Mathematics Theory and Applications, 2024)
This study aims to predict bitcoin prices using the time series method. One of the time series methods used is the ARIMA model. The data used is secondary data obtained from the site https://finance.yahoo.com in the form of monthly closing price data. Monthly closing price data starting from August 2017 to July 2022 totaling 60 data. The data obtained is used to predict bitcoin prices for the next 10 months, namely August 2022 to May 2023. The results show that the ARIMA(0,2,2) model is the best model chosen. The prediction results using the ARIMA model (0,2,2) for August 2022 to May 2023 are 25,674.46; 26018.57; 26,362.68; 26,706.79; 27050.90; 27,395.01; 27,739.13; 28083.24; 28,427.35 and 28,771.46. The results of this prediction show that the price of bitcoin will increase and the difference between the actual price and the predicted results is not much different from the actual data on the price of bitcoin.